2021
DOI: 10.7441/joc.2021.04.10
|View full text |Cite
|
Sign up to set email alerts
|

Bonds Between Earnings Management and Corporate Financial Stability in the Context of the Competitive Ability of Enterprises

Abstract: The financial health of enterprises and their continued profitability and competitiveness in the market are influenced considerably by the level of earnings achieved. Enterprises are forced to report the best possible results to demonstrate financial strength and competitiveness and to provide a good accounting for investors and creditors. Thus, the main objective of the study is to investigate whether there is any mutual dependence between corporate financial stability and earnings management. To measure thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…To ensure the accuracy of the BTD indicators, this study adopted the fixed residual method used by Desai and Dharmapala (2006) ( Tian et al, 2019 ) to calculate the tax difference indicator (CBTD), excluding the impact of accruals in the current year and the impact of earnings management ( Valaskova et al, 2021 ), as a measure of the level of tax aggressiveness of enterprises. The specific model is as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure the accuracy of the BTD indicators, this study adopted the fixed residual method used by Desai and Dharmapala (2006) ( Tian et al, 2019 ) to calculate the tax difference indicator (CBTD), excluding the impact of accruals in the current year and the impact of earnings management ( Valaskova et al, 2021 ), as a measure of the level of tax aggressiveness of enterprises. The specific model is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Drawing on previous research (Hanlon and Heitzman, 2010;Tian et al, 2019), the present study divides the measurement methods for tax avoidance indicators into the effective tax rate method and the tax difference method. Given the existence of many tax incentives and rebates for Chinese listed companies, the accuracy of using the effective tax rate method to measure tax To ensure the accuracy of the BTD indicators, this study adopted the fixed residual method used by Desai and Dharmapala (2006) (Tian et al, 2019) to calculate the tax difference indicator (CBTD), excluding the impact of accruals in the current year and the impact of earnings management (Valaskova et al, 2021), as a measure of the level of tax aggressiveness of enterprises. The specific model is as follows:…”
Section: Choose the Proper Variablesmentioning
confidence: 99%
“…earnings management and found that due to the threat of bankruptcy the firm manipulate their earnings to maintain competitiveness and credibility ( Valaskova et al, 2021 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Much focus has been placed on the relationship between the growth of the financial sector and that of the economy in the wake of the global financial crisis in 2008–2009 ( Jakimowicz and Rzeczkowski, 2019 ). This is because the financial system is designed to ensure that long-term business needs are met through capital flows ( Valaskova et al, 2021 ). The crisis demonstrated that the stability of the financial sector and the economy as a whole could be jeopardized by excessive risk-taking and a lack of financial system loss-absorbing capacity ( Hou et al, 2019 ; Latif et al, 2021 ; Iqbal S. et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%